Mathematical Identity of Students with Dyscalculia Tendency - Salisa, Resminati Dinda; Meilliasari, Meiliasari; Sovia, Anny (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aimed to investigate the factors that contribute to the formation of mathematical identity in students with a tendency towards dyscalculia. By understanding the mathematical identity of these students, we can gain insights into their interest in mathematics and identify appropriate interventions to meet their learning needs. This research followed a case study design and employed Creswell's model, which consists of six stages, for data analysis. The participants in this study were six junior high school students who displayed a tendency towards dyscalculia, as determined by the Dyscalculia Checklist. Of these students, three had a high tendency, two had a medium tendency, and one had a low tendency towards dyscalculia. A questionnaire was used to measure the participants' mathematical identity, which was categorized into three groups: three students had a positive mathematical identity, two students had a neutral identity, and one student had a negative identity. Six distinct components, namely the importance of mathematics, motivation, strategy, opportunity, obstacles, and the ability to perform, all played a unique role in shaping the students' mathematical identity. While these components, as well as the students' level of dyscalculia tendency, could influence their mathematical identity, it is crucial to acknowledge that the students' environment, both at school and at home, also contributed significantly to the development of their mathematical identity.